2022
DOI: 10.1111/jmft.12613
|View full text |Cite
|
Sign up to set email alerts
|

Changes in couple, parenting, and individual functioning following Family Expectations program participation

Abstract: The current study investigated changes in couple, parenting, and individual functioning following participation in Family Expectations, a relationship and parenting education program for new or expectant parents. The sample comprised 339 couples who participated in most sessions of the Family Expectations program and completed assessments at three different time points over a 12‐month period. Study analyses examined: (a) change shortly following completion of the program, (b) associations between short‐term ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This finding aligns with some previous studies that have shown a positive correlation between marital status and knowledge of climate change ( 29 , 30 ). Unmarried individuals may have more time to engage in educational activities ( 31 ). Residing in a nuclear family was positively associated with higher knowledge scores.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with some previous studies that have shown a positive correlation between marital status and knowledge of climate change ( 29 , 30 ). Unmarried individuals may have more time to engage in educational activities ( 31 ). Residing in a nuclear family was positively associated with higher knowledge scores.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in the context of projects funded by ACF, there are numerous nonsignificant findings but also evidence of positive effects on dimensions such as negative interaction (e.g., Devaney & Dion, 2010; Hsueh et al, 2012; Rhoades, 2015), overall relationship quality (Doss et al, 2020), stability (Moore et al, 2018), intimate partner violence (IPV; Moore et al, 2018), co‐parenting quality (Moore et al, 2018), and individual well‐being (Barton et al, 2022; Devaney & Dion, 2010; Roddy et al, 2020). There is also some evidence that the effects or mechanisms in such programs may be moderated by levels of sociodemographic disadvantage (Amato, 2014; Knopp et al, 2022), including in the program studied here (Ritchie et al, 2022).…”
Section: Brief History Of Research On Programs Funded By Acfmentioning
confidence: 99%